Sex chromosome evolution and speciation in Ficedula flycatchers. - Saetre, G; Borge, T; Lindroos, K; Haavie, J; Sheldon, B; Primmer, C; Syvänen, A (2003)
Speciation is the combination of evolutionary processes that leads to the reproductive isolation of different populations. We investigate the significance of sex-chromosome evolution on the development of post- and prezygotic isolation in two naturally hybridizing Ficedula flycatcher species. Applying a tag-array-based mini-sequencing assay to genotype single nucleotide polymorphisms (SNPs) and interspecific substitutions, we demonstrate rather extensive hybridization and backcrossing in sympatry. However, gene flow across the partial postzygotic barrier (introgression) is almost exclusively restricted to autosomal loci, suggesting strong selection against introgression of sex-linked genes. In addition to this partial postzygotic barrier, character displacement of male plumage characteristics has previously been shown to reinforce prezygotic isolation in these birds. We show that male plumage traits involved in reinforcing prezygotic isolation are sex linked. These results suggest a major role of sex-chromosome evolution in mediating post- and prezygotic barriers to gene flow and point to a causal link in the development of the two forms of reproductive isolation.